Flame Atomic Aabsorption Spectrometric Determination of Gold by Solid Phase Extraction Using Modified Nanometer Titanium Dioxide as Sorbent - Liu, Weijuan; Xu, Yiran; Dai, Yun; Wang, Yaming; Hu, Qiufen (Asian Journal of Chemistry, 2010)
The nanometer titanium dioxide immobilized on silica gel (NTDS) loaded with 5-(2-hydroxy-5-nitrophenylazo)-thiorhodanine (HNATR) was prepared and its solid phase extraction of gold was investigated. Gold could be adsorbed quantitatively when the gold-bearing samples flew through the column in 1.0 mol/L in phosphoric acid medium. The gold enriched on the column was eluted with 0.1 mol/L of sodium thiosulfate, realizing the high enrichment factor of low concentration gold and the separation of most interfering ions. Gold in the eluant was measured by flame atomic absorption spectrometry. Under the chosen experimental conditions, Beer's 1aw was obeyed in the range of 0.05- 3.0 μg/mL for Au(III) with the correlation coefficient (r) of 0.9996. This method was used to determination of gold in ore and environmental waste samples with RSD in the range of 2.2-3.2 % and addition recovery of 88-104 %.